Climate Resilient Technologies/Practices to Support Pond Aquaculture and Beel Fisheries under APART, Assam, India - Chand, Bimal; Rajendran, Suresh; Chadag, Vishnumurthy Mohan (WorldFish, 2022)
One of the probable reasons for this is the vulnerability of the state to the climate induced hazards like flood, erosion, drought, etc. which are adversely impacting the fishery sector of the state. In the year 2018, the state has launched World Bank assisted ‘Assam Agribusiness and Rural Transformation Project (APART)’ with fisheries as a subcomponent. Through this project, WorldFish is extending the technical support to the state with its international experience and expertise. One of the focus areas of WorldFish is climate-proofing the fishery sector of the state by developing and promoting climate-resilient technologies. The purpose is to counter the negative impacts of climate change, mainly the pond aquaculture and Beel fisheries, and to push the fish production of the state upward. The outcome of the present study would support the resilience of fisheries and aquaculture production systems in order to increase fish production and reduce the risks associated with climate change, in the targeted districts of Assam.